2003
DOI: 10.1536/jhj.44.385
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in the Electrophysiologic Properties of the Atrium in Patients with no History of Atrial Fibrillation

Abstract: SUMMARYAlthough atrial fibrillation is a common arrhythmia, especially in the elderly, little is known about age-related changes in the electrophysiologic properties of the atrium. The aim of this study was to analyze the effect of aging on atrial vulnerability to atrial fibrillation.An electrophysiologic study was performed in 45 patients with no history of atrial fibrillation, Wolff-Parkinson-White syndrome, structural heart disease, or conditions with potential effects on cardiac hemodynamic or electrophysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
(41 reference statements)
1
12
0
Order By: Relevance
“…Interactions of age as a continuous variable: CAI >5, P = 0.04; CSA-CSR, P = 0. the effects of advanced age and SDB may be multiplicative. For example, the pathophysiologic insults of SDB, including intermittent hypoxia, autonomic imbalance, and intrathoracic pressure swings, may have more pronounced effects on atrial arrhythmogenesis when superimposed on the aged heart, which has an electrophysiologic substrate different from that of younger individuals (47)(48)(49)(50)(51). Enhanced impulse generation due to increased automaticity, triggered activity, and reentrant circuits within the atria and pulmonary veins are considered to be responsible for AF initiation and maintenance in the elderly and at a specific age threshold may be more likely to occur as a pathophysiologic response to SDB-induced physiologic stress (48,50,52).…”
Section: Discussionmentioning
confidence: 99%
“…Interactions of age as a continuous variable: CAI >5, P = 0.04; CSA-CSR, P = 0. the effects of advanced age and SDB may be multiplicative. For example, the pathophysiologic insults of SDB, including intermittent hypoxia, autonomic imbalance, and intrathoracic pressure swings, may have more pronounced effects on atrial arrhythmogenesis when superimposed on the aged heart, which has an electrophysiologic substrate different from that of younger individuals (47)(48)(49)(50)(51). Enhanced impulse generation due to increased automaticity, triggered activity, and reentrant circuits within the atria and pulmonary veins are considered to be responsible for AF initiation and maintenance in the elderly and at a specific age threshold may be more likely to occur as a pathophysiologic response to SDB-induced physiologic stress (48,50,52).…”
Section: Discussionmentioning
confidence: 99%
“…[3944] Both effective refractory period, which primes the heart for atrial reentrant circuits, and percent maximum atrial fragmentation, a measure reflective of AF inducibility, correlated with age in participants with no risk factors for AF. [41,42,45,46] Other work showed significant pulmonary vein electroanatomic changes with age which may be secondary to age-related atrial fibrosis. [29,44,47,48] Previous work on this topic has not examined the effects of age on the PLMS-AF relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst most animal and human studies have shown that aged atria have an increased propensity to develop AF [8793], some studies in elderly AF patients have yielded conflicting results although these could have been influenced by underlying pathology or treatment in patients [9496]. Increased atrial ERP has been noted in these studies which could be sufficient to overcome any other arrhythmogenic remodelling.…”
Section: Electrophysiological and Structural Alterations In Aged Amentioning
confidence: 99%